2016
DOI: 10.1038/ijo.2016.136
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of sedentary behaviour using accelerometers

Abstract: Background:Sedentary behaviour (SB) is an important risk factor for a number of chronic diseases. Although gaps remain in our knowledge of the elements of SB most associated with reduced health outcomes, measuring SB is important, especially in less active patient populations where treatment-related changes may be seen first in changes in SB.Methods:We review current published work in the measurement of SB to make recommendations for SB measurement in clinical studies.Results:To help move our understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 18 publications
0
58
2
1
Order By: Relevance
“…Further research exploring sedentary behavior in people with PD could consider using a device worn on the thigh, such as the activPAL (PAL Technologies Ltd, Glasgow, UK), which is more likely to accurately detect sitting and lying time. 29 PD impairments contributed to the difference in step and activity counts. The multivariate regression analysis identified that more tremor and dyskinesia accounted for 19% of the variability in the difference in step counts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further research exploring sedentary behavior in people with PD could consider using a device worn on the thigh, such as the activPAL (PAL Technologies Ltd, Glasgow, UK), which is more likely to accurately detect sitting and lying time. 29 PD impairments contributed to the difference in step and activity counts. The multivariate regression analysis identified that more tremor and dyskinesia accounted for 19% of the variability in the difference in step counts.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore possible that the waist monitor in the present study was overestimating sedentary time by including standing time. Further research exploring sedentary behavior in people with PD could consider using a device worn on the thigh, such as the activPAL (PAL Technologies Ltd, Glasgow, UK), which is more likely to accurately detect sitting and lying time …”
Section: Discussionmentioning
confidence: 99%
“…However, no single measure captures all aspects of sedentary behaviour [61], and there are alternative ways of conceptualising and operationalizing it [62] and one of these measures might be more strongly influenced by the neighbourhood and social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Energy expenditure and physical activity (light, moderate to vigorous, and vigorous activity) were calculated as previously described (Bressa et al, 2017). Sedentary behavior was characterized by the number of sedentary bouts (period of consecutive minutes where the accelerometer registers < 100 counts/min) and sedentary breaks (period of at least 1 min where the accelerometer registers ≄ 100 counts/min following a sedentary bout) and the total time spent in them (Byrom et al, 2016).…”
Section: Physical Activity and Sedentary Behavior Determinationmentioning
confidence: 99%